Марк Алданов в виленском зеркале [Mark Aldanov in the Vilna Mirror] - Lavrinec, Pavel (Slavica Revalensia, 2026)
The purpose of the study is to reconstruct the literary reputation of Mark Aldanov in one of the local segments of the Russian diaspora during the interwar period. The study is based on the assumption that similar mechanisms for the formation of literary reputations also worked in other centers of Russian dispersion. The article uses information from archival documents in the library of the Vilna Russian Society and publications in periodicals, which indicates the accessibility of Aldanov’s texts to a Vilna reader. I provide an overview of the writer’s place in Russian emigré and European literatures as accessed in a series of articles published between 1929 and 1938 by Dorofey Bokhan, the leading critic of the Vilna Russian press, as well as in the only “study of the characteristics of [Aldanov’s] works” (1935) by Ksenia Kostenich and the only review (of the novel The Beginning of the End, 1939) by Bokhan. The study allows us to conclude that Mark Aldanov was seen as one of the major writers of the Russian diaspora, a reformer of the historical novel, as well as both a master of impeccable style and of the psychological portrait.